Comparison of learning models to predict LDPE, PET, and ABS concentrations in beach sediment based on spectral reflectance - Faisal, Raiyan Huda; Florina Stephanie, Richard; Ishraq, Rahman; Saeid, Moradi; ClarenceTay, Yuen Hua; ChristabelAnfeld, Sim Wanwen; Ting, Lik Fong; Aazani, Mujahid; Moritz, Müller (Springer Nature Limited, 2023)
Microplastic (MP) contamination on land has been estimated to be 32 times higher than in the oceans, and yet there is a distinct lack of research on soil MPs compared to marine MPs. Beaches are bridges between land and ocean and present equally understudied sites of microplastic pollution. Visible-nearinfrared (vis–NIR) has been applied successfully for the measurement of refectance and prediction of low-density polyethylene (LDPE), polyethylene terephthalate (PET), and polyvinyl chloride (PVC) concentrations in soil. The rapidity and precision associated with this method make vis–NIR promising. The present study explores PCA regression and machine learning approaches for developing learning models. First, using a spectroradiometer, the spectral refectance data was measured from treated beach sediment spiked with virgin microplastic pellets [LDPE, PET, and acrylonitrile butadiene styrene (ABS)]. Using the recorded spectral data, predictive models were developed for each microplastic using both the approaches. Both approaches generated models of good accuracy with R2 values greater than 0.7, root mean squared error (RMSE) values less than 3 and mean absolute error (MAE) < 2.2. Therefore, using this study’s method, it is possible to rapidly develop accurate predictive models without the need of comprehensive sample preparation, using the low-cost option ASD HandHeld 2 VNIR Spectroradiometer.